Analisis Faktor Konfirmatori untuk Mengetahui Faktor-Faktor yang Mempengaruhi Prestasi Mahasiswa Program Studi Statistika FMIPA Universitas Mulawarman - Andini Juita Sari; Desi Yuniarti; Sri Wahyuningsih (Program Studi Statistika FMIPA Universitas Mulawarman, 2017)
Confirmatory factor analysis is one part of the multivariate analysis. In this study conducted a confirmatory factor analysis of statistics student of Mulawarman University in 2013, 2014, and 2015 of 159 with research aims to determine the factors affecting the achievement of students. The analysis showed that, is influenced by four latent variables are latent variables background (ξ1) with three indicator variables of the relation with family (X1), parental (X2), and the motivation of the family (X3). Latent variables learning environment outside the campus (ξ2) with two indicator variables are the concentrations studied (X6) and the completion of tasks (X7). Latent variables campus facilities (ξ3) with indicator variables study room (X8), reading room of statistics (X9), wifi (X10), and computer facilities laboratory (X11). Latent variable students perceptions of lecturers (ξ4) with two indicator variables the learning system of lecturers (X14) and system administration duties of lecturers (X15). Indicator variables give large contribute affect to student achievement is the completion of the task (X7) rated loading factor of 0.89.